Effects of digital transformation on electricity sector growth and productivity: A study of thirteen industrialized economies. (February 2022) - Vu, Khuong; Hartley, Kris
Abstract: This study examines growth patterns and sources of labour productivity growth and catch-up in the electricity sector. The study uses decomposition analysis to examine 13 industrialized economies from 2000 to 2015, a period of high growth in the sector. The study finds that total factor productivity and digital assets are the most powerful drivers of labour productivity growth and catch-up, while non-ICT assets have only a minor effect. Furthermore, labour quality outpaces R&D as a determinant of productivity. This study has implications for labour and industrial policy in the context of technological transformation and institutional restructuring in the electricity sector. Highlights: This study examines growth patterns and sources of labor productivity growth and catch-up in the electricity sectors of the 13 industrialized economies. The six sources of labor productivity include: non-ICT assets, ICT hardware, intangible software and database assets, intangible research and development assets, labor quality, and total factor productivity. Total factor productivity and digital assets are the most powerful drivers of labor productivity growth and catch-up, while non-ICT assets have only a minor effect. Labor quality outperforms investment in R&D as a determinant of productivity. This study has implications for labor and industrial policy in an era of change and restructuring in the electricity sector.